Kidney function in cachexia and sarcopenia: Facts and numbers - Masatsugu Okamura; Masaaki Konishi; Javed Butler; Kamyar Kalantar‐Zadeh; Stephan vonHaehling; Stefan D. Anker (Wiley, 2023)
Abstract Cachexia, in the form of unintentional weight loss >5% in 12 months or less, and secondary sarcopenia in the form of muscle wasting are serious conditions that affect clinical outcomes. A chronic disease state such as chronic kidney disease (CKD) often contributes to these wasting disorders. The purpose of this review is to summarize the prevalence of cachexia and sarcopenia, their relationship with kidney function, and indicators for evaluating kidney function in patients with CKD. It is estimated that approximately half of all persons with CKD will develop cachexia with an estimated annual mortality rate of 20%, but few studies have been conducted on cachexia in CKD. Hence, the true prevalence of cachexia in CKD and its effects on kidney function and patient outcomes remain unclear. Some studies have highlighted the concept of protein‐energy wasting (PEW) which usually include sarcopenia and cachexia. Several studies have examined kidney function and CKD progression in patients with sarcopenia. Most studies use serum creatinine levels to estimate kidney function. However, creatinine may be influenced by muscle mass, and creatinine‐based glomerular filtration rate may overestimate kidney function in patients with reduced muscle mass or muscle wasting. Cystatin C, which is least affected by muscle mass, has been used in some studies, and creatinine‐to‐cystatin‐C ratio has emerged as an important prognostic marker. A previous study incorporating 428 320 participants reported that participants with CKD and sarcopenia had a 33% higher hazard of mortality compared with those without (7% to 66%, P = 0.011), and that those with sarcopenia were twice as likely to develop end‐stage kidney disease (hazard ratio: 1.98; 1.45 to 2.70, P < 0.001). Future studies on cachexia and sarcopenia in patients with CKD are needed to report rigorously defined cachexia concerning kidney function. Moreover, in studies on sarcopenia with CKD, it is desirable to accumulate studies using cystatin C to accurately estimate kidney function.